Imaging features and outcomes in patients with ruptured hepatocellular carcinoma following transcatheter arterial chemoembolization: a retrospective clinical study. Issue 4 (April 2021) - Zhao, Wenpeng; Hou, Xiaopu; Li, Honglu; Guo, Jiang; Cai, Liang; Duan, Youjia; Du, Hongliu; Shao, Xihong; Diao, Zhenying; Li, Changqing
Objective: To summarize and analyze the imaging features and outcomes of patients with ruptured hepatocellular carcinoma (HCC) following transcatheter arterial chemoembolization (TACE). Methods: We investigated all consecutive patients with HCC who received standardized TACE based on our hospital database. Ruptured HCCs were divided into three types according to their relationship with the liver capsule, determined by computed tomography or magnetic resonance imaging scans: Type I, portion of tumor cambered outwards ≤30%; Type II, portion of tumor cambered outwards >30% and <50%; and Type III, portion of tumor cambered outwards ≥50%. Results: There were 54, 40, and 26 patients with Type I, II, and III HCCs, respectively. Among these, eight patients developed ruptured tumors within 2 weeks after TACE, including one, two, and five patients with type I, II, and III ruptured HCCs, respectively. Patients with type III HCCs had a shorter median survival time than patients with type I–II HCCs. Conclusions: Patients with type III HCCs might have a higher re-rupture rate and benefit less from emergency arterial embolization procedures than patients with type I–II HCCs.